2020
DOI: 10.1037/ccp0000597
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness and acceptability of empirically supported treatments in gender minority youth across four randomized controlled trials.

Abstract: Objective: Gender minority youth (i.e., children/adolescents whose gender identity and/or expression is inconsistent with their birth-assigned sex) experience elevated rates of emotional and behavioral problems relative to cisgender youth (who identify with their birth-assigned sex), which are not intrinsic to gender identity but attributable to unique minority stressors. Although empirically-supported treatments have proven effective in treating these mental health concerns generally, randomized controlled tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 100 publications
0
22
0
Order By: Relevance
“…One additional study meeting the inclusion criteria was identified from citation searches 32. Therefore, 10 studies were included in this review 32–41…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One additional study meeting the inclusion criteria was identified from citation searches 32. Therefore, 10 studies were included in this review 32–41…”
Section: Resultsmentioning
confidence: 99%
“…There were four cohort studies,36 39–41 two pre–post studies32 34 (one of which included analysis of open-ended survey responses in addition to outcome data34), three mixed methods,33 35 37 and one was a secondary analysis of intervention group data from four randomised controlled trials (RCTs)38 (the individual RCTs were excluded because they presented combined results for those experiencing and not experiencing gender dysphoria/incongruence). Five studies included a comparator group of children and/or adolescents not experiencing gender dysphoria/incongruence36 38–41 and one included a historical cohort of adolescents with gender dysphoria/incongruence 33. Half of the studies were conducted in the US (n=5),32 35 38 40 41 two in the UK36 37 and single studies from Australia,33 Canada34 and New Zealand 39 Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Pertinent to Venturo-Conerly et al's review, these inequities have been demonstrated in youth modular psychotherapy. Specifically, Hollinsaid et al (2020) found that gender minority youth across four randomized controlled trials of modular psychotherapy exhibited less symptom reduction and lower treatment satisfaction compared to cisgender youth.…”
Section: Stigma Clinical Judgment and Clinical Outcomesmentioning
confidence: 99%
“…To improve our field's ability to examine stigma in all intervention research, we conclude with recommendations for broader mental health treatment research: 1. To facilitate analyses of treatment outcomes for different stigmatized groups (e.g., Hollinsaid et al, 2020), recruit large and diverse samples of youth reflecting multiple stigmatized identities and comprehensively collect data on these identities (Kataoka et al, 2010;Lau et al, 2010;Santelli et al, 2003).…”
Section: Summary and Recommendations For Broader Mental Health Treatm...mentioning
confidence: 99%